2003
DOI: 10.1093/ije/dyg084
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood deprivation and health: does it affect us all equally?

Abstract: Evidence is accumulating that the place where a person lives may influence their health, even after accounting for individual risk factors, 1-10 although some studies have found no independent effects of area on health once individual factors have been controlled for. [11][12][13] On the whole, the literature points to relatively small effects of area characteristics in comparison with the larger effects of individual socioeconomic position, 10 although most findings are based on secondary analysis of existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
313
4
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(341 citation statements)
references
References 36 publications
(29 reference statements)
17
313
4
7
Order By: Relevance
“…27 However, data linking neighborhood education level with asthma is sparse. The protective influence of increased education level in a child's neighborhood may represent an important construct for increased access to collective resources and capital, 28 medical care, or healthy behaviors, reduced stress, or decreased allergens. For example, a greater proportion of individuals with higher education may indicate greater social capital and therefore the potential to improve neighborhood conditions and reduce neighborhood disorder 29 -which may in turn reduce an individual's negative psychophysiological response to the larger neighborhood environment.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, data linking neighborhood education level with asthma is sparse. The protective influence of increased education level in a child's neighborhood may represent an important construct for increased access to collective resources and capital, 28 medical care, or healthy behaviors, reduced stress, or decreased allergens. For example, a greater proportion of individuals with higher education may indicate greater social capital and therefore the potential to improve neighborhood conditions and reduce neighborhood disorder 29 -which may in turn reduce an individual's negative psychophysiological response to the larger neighborhood environment.…”
Section: Discussionmentioning
confidence: 99%
“…Preventive health care and increased participation in medical checkups may also be a characteristic of a neighborhood with greater social capital, thereby enabling residents to identify potential health problems prior to onset. Social capital has the potential to reduce individuals' focus on disease and illness, potentially explaining why individuals from disadvantaged neighborhoods are more likely to self-rate their general health as poor, compared to their counterparts residing in less disadvantaged areas (25). Neighborhoods of greater social capital share "norms" that influence preventive health behaviors such as physical activity and lower caloric intake, both of which are key predictors of body habitus and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between individual and neighbourhood-level socioeconomic factors were assessed by Yen and Kaplan 21 but no interaction effects were found. Stafford, in the analysis of mental health in Whitehall II participants, 18 reported non-significant interaction between neighbourhood deprivation and individual occupational class. As shown above, virtually all of the existing research on social and economic factors and depression came from Western Europe and Northern America.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, over the recent decades there have been several multilevel studies on this topic. 8,[14][15][16] Most of these studies have shown an association between neighbourhood SES and depression or depressive symptoms [14][15][16][17][18] , although some studies found no association after adjusting for individual-level socioeconomic factors 19,20 . Two longitudinal studies 21,22 reported that the SES of neighbourhood was associated with incidence of depression independent from individual socioeconomic status and other individual risk factors.…”
Section: Introductionmentioning
confidence: 99%